Everyday ethnicity in Sri Lanka Up-country Tamil identity politics - Bass, Daniel (London ; New York : Routledge, 2013)
Focusing on notions of diaspora, identity and agency, this book examines ethnicity in war-torn Sri Lanka. It highlights the historical development and negotiation of a new identification of Up-country Tamil amidst Sri Lanka's violent ethnic politics. Over the past thirty years, Up-country (Indian) Tamils generally have tried to secure their vision of living within a multi-ethnic Sri Lanka, not within Tamil Eelam, the separatist dream that ended with the civil war in 2009. Exploring Sri Lanka within the deep history of colonial-era South Asian plantation diasporas, the book arg
Keywords: Malaiyaha Tamil (Sri Lankan people) -- Ethnic identity; Malaiyaha Tamil (Sri Lankan people) -- Government policy -- Sri Lanka; Tamil diaspora; Malaiyaha Tamil (Sri Lankan people) -- Politics and government; Identity politics -- Sri Lanka; Sri Lanka -- Race relations -- Political aspects; Sri Lanka -- Politics and government -- 1978-